Enhancing writing skills - Elufiede, Oluwakemi; Murray, Tina; Boden, Carrie J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Enhancing Writing Skills includes conference presentation papers from the Carnegie Writers, Inc. 1st Annual Conference. The anthology provides published and aspiring writers resources for sustaining, enhancing and evaluating their writing skills. The chapter themes focus on genre-based writing, creativity in writing, mechanics of writing, academic writing, and writing as a business. Enhancing writing skills is beneficial to diverse writers as it impacts the community, working, and educational environments. Anthology goals and ojbjectives: - Enable writers to learn from other writers for the development of networking relationships and professional development. - Assist writers with techniques on sustaining their writing talents in their chosen genre or various genres. - Provide meaningful publishing resources related to non-traditional and traditional publication venues. - Enhance writers understanding for marketing strategies in the 21st century.
"The themes of this book are based on those from the inaugural conference of The Carnegie Writers, Inc., held November 14, 2015 in Nashville, TN"--Introduction.
Keywords: Creative writing -- Study and teaching -- Congresses.; Adult education -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; electronic books